Sinonasal angiosarcoma: a rare case of recurrent vascular malignancy managed with endoscopic excision and radiotherapy - Krishna, Aswathi; Cheriyil, Surya; Wilfred, Manu; Menon, Pramod (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Angiosarcoma is an aggressive endothelial malignancy that is rarely found in the nasal cavity. Objectives of the study were to present a rare case of sinonasal angiosarcoma, treated via endoscopy and radiotherapy A 50-year-old hypertensive woman presented with one month of recurrent left epistaxis and nasal obstruction. Endoscopy revealed a firm, bleeding reddish-black mass medial to the middle turbinate. CT imaging showed a heterogeneously enhancing lesion extending into the nasopharynx and ethmoidal cells. Endoscopic excision revealed a 5×2.5×1.5 cm lesion; histopathology showed retiform and capillary vascular channels with endothelial hob nailing and focal necrosis. Immunohistochemistry was positive for CD34, BCL2, CD99; Ki 67 was ~25% with possibility of hemangioen-thothelioma. Recurrence appeared at three months and was excised, confirming angiosarcoma. The patient underwent 30 cycles of radiotherapy. Sinonasal angiosarcoma is aggressive with high recurrence risk. Thorough histopathological evaluation, combined treatment, and close follow-up are essential.